2023
DOI: 10.1021/acs.inorgchem.3c00418
|View full text |Cite
|
Sign up to set email alerts
|

Unique Metal–Ligand Interplay in Directing Discrete and Polymeric Derivatives of Isomeric Azole-Carboxylate. Varying Electronic Form, C–C Coupling, and Receptor Feature

Abstract: This article dealt with the ruthenium and osmium derivatives of isomeric 1H-indazole-3-carboxylic acid/2H-indazole-3carboxylic acid (H 2 L1) and 1H-benzimidazole-2-carboxylic acid (H 2 L2) along with the π-acidic bpy (bpy = 2,2′-bipyridine) and pap (pap = 2phenylazopyridine) co-ligands. It thus extended structurally authenticated monomeric ([(bpy) 2 Ru II (HL1 − )]ClO 4 [1]ClO 4 , (pap) 2 Ru II (L1 2− ) 2, (bpy) 2 Os II (L1 2− ) 3, (pap) 2 Os II (L1 2− ) 4, (bpy) 2 Ru II (L2 2− ) 5, (bpy) 2 Os II (L2 2− ) 8, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…In the presence of a reducing agent, these compounds induce DNA damage by ROS generation. Cytotoxicity studies with different cancer cell lines revealed that complexes [Cu(tnz) 2 (µ-Cl)Cl] 2 and [Cu(tnz) 2 Br 2 ] showed the highest cytotoxicity, while being moderately toxic to normal cells [26,27] Generally, the reported cytotoxic transition metal compounds have been synthesized using chelating ligands [28][29][30][31][32][33][34]. The results with non-chelating ligands, tinidazole and clotrimazole [35][36][37][38][39][40][41][42], have shown that weak interactions, such as hydrogen bonding, electrostatic interactions, π stacking, lp•••π or hydrophobic contacts, as well as geometry and redox properties, have an important role in the biological activity of coordination compounds with monocoordinated ligands.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of a reducing agent, these compounds induce DNA damage by ROS generation. Cytotoxicity studies with different cancer cell lines revealed that complexes [Cu(tnz) 2 (µ-Cl)Cl] 2 and [Cu(tnz) 2 Br 2 ] showed the highest cytotoxicity, while being moderately toxic to normal cells [26,27] Generally, the reported cytotoxic transition metal compounds have been synthesized using chelating ligands [28][29][30][31][32][33][34]. The results with non-chelating ligands, tinidazole and clotrimazole [35][36][37][38][39][40][41][42], have shown that weak interactions, such as hydrogen bonding, electrostatic interactions, π stacking, lp•••π or hydrophobic contacts, as well as geometry and redox properties, have an important role in the biological activity of coordination compounds with monocoordinated ligands.…”
Section: Introductionmentioning
confidence: 99%